Distributional impact of tax and welfare policies: COVID-related policies and Budget 2021 - Roantree, Barra (The Economic and Social Research Institute, 2020)
In this article, we assess the impact of the COVID-19 pandemic on unemployment in Ireland and estimate how family incomes have changed as a result of increased unemployment, calibrated to administrative sources for end-August. We then show how the direct and indirect tax and welfare measures enacted prior to Budget 2021 have helped to cushion pandemic-related income losses. Lastly, we assess the impact of Budget 2021 measures. We find that pandemic-related unemployment could have decreased household income by an average of 7 per cent across the population, with significantly larger losses for those who lost their jobs. Thanks to the initial policy response in the form of the PUP, wage subsidy and standard rate VAT cut, household income fell instead by 3 per cent on average. These losses are sharpest at the upper end of the income distribution, for the young, and for those in certain hard-hit sectors such as hospitality. The impact of Budget 2021, while less costly than the pre-budget measures, is similar in pattern, with above average gains for the bottom two-fifths of the income distribution and lower than average gains for those at the upper end. Without these interventions, income inequality would have increased substantially. Instead, our simulations suggest that the COVID-related interventions stabilised disposable income inequality, a significant feat given the job losses experienced. At risk of poverty rates were also stabilised by COVID- related policies but there is a risk that these indices may increase significantly once these supports are withdrawn. We conclude with some brief reflections on some of the challenges facing the government in the coming years.
PUBLISHED
Keywords: Inclusive Society